2016
DOI: 10.1016/j.ejphar.2016.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dopamine D1-like and D2-like antagonists on cocaine discrimination in muscarinic receptor knockout mice

Abstract: Muscarinic and dopamine brain systems interact intimately, and muscarinic receptor ligands, like dopamine ligands, can modulate the reinforcing and discriminative stimulus (SD) effects of cocaine. To enlighten the dopamine/muscarinic interactions as they pertain to the SD effects of cocaine, we evaluated whether muscarinic M1, M2 or M4 receptors are necessary for dopamine D1 and/or D2 antagonist mediated modulation of the SD effects of cocaine. Knockout mice lacking M1, M2, or M4 receptors, as well as control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…Therefore, we focus on the M 4 receptor here. M 4 -KO mice display an increase in cocaine self-administration compared to controls (Schmidt et al, 2011;Thomsen and Caine, 2016), similar to that observed in D 3 -KO mice described above. Increased cocaine selfadministration in M 4 -KO mice was observed at intermediate doses of cocaine under both a FR and a PR schedule of reinforcement, manifested as an upward shift of cocaine selfadministration dose-response curves (Schmidt et al, 2011).…”
Section: Decreased M 4 R Expression Is a Risk Factor For Cocaine And Alcohol Usesupporting
confidence: 85%
“…Therefore, we focus on the M 4 receptor here. M 4 -KO mice display an increase in cocaine self-administration compared to controls (Schmidt et al, 2011;Thomsen and Caine, 2016), similar to that observed in D 3 -KO mice described above. Increased cocaine selfadministration in M 4 -KO mice was observed at intermediate doses of cocaine under both a FR and a PR schedule of reinforcement, manifested as an upward shift of cocaine selfadministration dose-response curves (Schmidt et al, 2011).…”
Section: Decreased M 4 R Expression Is a Risk Factor For Cocaine And Alcohol Usesupporting
confidence: 85%
“…The experimental procedure was as previously described (Thomsen et al, 2012, 2010; Thomsen and Caine, 2016). In brief, mice were trained to discriminate 10 mg/kg cocaine from saline, under an FR 10 schedule of food reinforcement.…”
Section: Methodsmentioning
confidence: 99%
“…The active and ineffective doses of drugs were selected by the literature studies. 9,[19][20][21][22][23] The effective and sub-effective doses of SCE have been selected on the basis of the results in the forced swim test as shown in Fig. 1, and confirmed in the tail suspension test (data not shown).…”
Section: Drugs and Treatmentsmentioning
confidence: 99%